Interferon gamma replacement as salvage therapy in chronic pulmonary aspergillosis: effects on frequency of acute exacerbation and all-cause hospital admission. Issue 6 (30th March 2020) - Monk, Edward J M; Harris, Chris; Döffinger, Rainer; Hayes, Gemma; Denning, David W; Kosmidis, Chris
Abstract : Chronic pulmonary aspergillosis (CPA) is often poorly responsive to antifungal treatment; secondary infections increase morbidity/mortality, particularly in progressive cases. Interferon gamma (IFNγ) has been implicated in not only Aspergillus control but also bacterial clearance. Clinical notes of patients with CPA treated with IFNγ (2011–2018) were retrospectively hand-searched. In patients treated for >12 months (n=20), the frequency of acute exacerbation reduced from 3.1 to 1.4 episodes/year (p=0.006) in the 12 months after treatment initiation compared with the 12 months before. A significant reduction in the frequency of hospital admissions/year was also observed (0.8 to 0.3, p=0.04). These findings support further prospective studies.